Factors linked to poor glycemic control in an outpatient diabetic clinic: a cross-sectional study in Saint-Nicolas Hospital, Haiti - Ludentz Dorcélus; Emmanuel R. Alexandre; Charnee M. Villemenay; Scaïde U. Benjaminel; Eddie Charles (Journal of Global Health Reports)
# Background